1997
DOI: 10.1021/ac9605962
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Characterization of Gold Colloid Monolayers:  A Comparison of Four Techniques

Abstract: Atomic force microscopy (AFM), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), and near-field scanning optical microscopy (NSOM) have been used to characterize the nanostructure of Au colloid-based surfaces. Because these substrates are composed of particles whose dimensions are known prior to assembly, they are well-suited for a critical comparison of the capabilities and limitations of each nanoscale imaging technique. The three criteria for this comparison, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
173
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(186 citation statements)
references
References 55 publications
13
173
0
Order By: Relevance
“…The Au nanoparticles synthesized using citrate-reduction method are negatively charged: they are adsorptive to a positively charged aminemodified surface. [16][17][18] Keating et al analyzed an adsorption isotherm of 12-nm-diameter Au nanoparticles on an APTMSderivatized glass surface, as examined using UV/vis spectrophotometry. 18 Although values a were smaller because of the larger nanoparticles and the fact that K was larger than that in their study, we found that the respective signs of g¢ were opposite for 12-nm and 30-nm nanoparticles.…”
Section: Kcmentioning
confidence: 99%
See 2 more Smart Citations
“…The Au nanoparticles synthesized using citrate-reduction method are negatively charged: they are adsorptive to a positively charged aminemodified surface. [16][17][18] Keating et al analyzed an adsorption isotherm of 12-nm-diameter Au nanoparticles on an APTMSderivatized glass surface, as examined using UV/vis spectrophotometry. 18 Although values a were smaller because of the larger nanoparticles and the fact that K was larger than that in their study, we found that the respective signs of g¢ were opposite for 12-nm and 30-nm nanoparticles.…”
Section: Kcmentioning
confidence: 99%
“…5,[11][12][13] On the other hand, several research groups have revealed that Au nanoparticles synthesized using a citrate-reduction method are strongly adsorbed onto a glass surface coated with bifunctional-organosilanes. [14][15][16][17][18] Their approach was later applied for fabricating an Au-nanoparticle-monolayer-based LSPR optical sensor for use in biomolecule interaction measurements. Several groups have reported the potential use of such nanoparticles for molecular interaction analyses of Au nanoparticle monolayers on a glass substrate surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2]), a value of 150 nm is obtained for particle lateral diameter (corresponding to the radius r c in Eq. [2]). A mean value of 17…”
Section: Table 4 Statistics On Afm Imaged Nonmagnetic Particlesmentioning
confidence: 99%
“…Previous studies using AFM on colloidal particles imaged mainly gold particles for comparison with other imaging techniques (2) or for applications as tip characterizers and calibrating samples as well as for characterization of coadsorbed biomolecules (3). Recently, images of silica and polystereneencapsulated silica particles were presented (4) to confirm the synthesis outcome.…”
Section: Introductionmentioning
confidence: 99%